Clinical surgery-oriented subject librarian services in medical colleges and schools - He Qiang (Sciendo, 2018)
Regarding subject librarian services for clinical studies, researchers outside China have been focusing on subject service performance, evidence-based medicine, and comprehensive consulting services. In contrast, Chinese researchers have concentrated on service systems and methods but have not established mature systems and methods for clinical surgery-oriented services. Therefore, subject librarians in medical schools should become involved in clinical research and expand their perspective on medical library research. In addition, they should collaborate with clinicians to improve the overall level of research in hospitals while increasing the impact of subject librarian services in medical colleges and schools.